Analysis of The Cost and Time Comparison of Diversion Methods and Dewatering of Box Culvert Work - Susanti, Irriene Indah; Ifo HS, Dewitri Asti (Journal of World Conference (JWC), 2020)
Low geographical conditions and flowed by many rivers and the reduction of retention ponds in Jakarta, then built a reservoir. However, during the implementation period, it was delayed by 9.74%. One of the things that can be done to overcome delays is to choose a method of implementation. The method is diversion and dewatering. The results of the analysis are expected to produce a large comparison of the costs and time of each method. From the analysis results, the cost of implementing the method of soil and rock diversion in the box culvert work is Rp. 363,935,953, while the sandbag diversion method is Rp. 332,805,831. For box culvert work using open pumping dewatering method, the required cost is Rp. 394,637,510. From these data, it was concluded that the difference in the cost of diversion sandbag and rock soil was Rp. 31,130,122. While rock soil and dewatering diversion are Rp. 30,701,557. As well as sandbag diversions with dewatering of Rp. 61,831,679. The results of observations of the implementation time obtained the conclusion that the work of box culvert with sandbag diversion method takes 35 days, and rock soil diversion 49 days while dewatering 63 days. By time comparison the sandbag diversion method is 14 days faster than rock soil diversion, and 28 days compared to the dewatering method. From these data, it can be concluded that in terms of cost and time, the sandbag diversion method is more economical and efficient than the other two methods.